Discourses of Islamic Performance Ratio Based on Tawhid String Relationship - Lucky Nugroho; Tatik Mariyanti (Journal of Islamic Economics and Social Science (JIESS), 2021)
This conceptual review aims to analyze the performance measurement of Islamic banks based on sharia principles using the Tawhid String Relationship (TSR) concept. The method used is descriptive and qualitative, where the data sources from previous studies in the form of journals and books related to the research topic. Therefore, the formulation of the problem in this conceptual review consists of research questions as follows: (i) How should the performance of Islamic banks be based on the perspective of the Tawhid String Relationship (TSR)?; (ii) How is the implementation of the TSR concept on the performance of Islamic banks?; (iii) What is the role of the government in supporting to achieve of excellence Islamic bank performance?. The study results are that Islamic banks based on TSR have four crucial pillars: spiritual aspects, financial aspects, social aspects, and environmental aspects. Furthermore, based on this, the performance measurement of Islamic banks needs to be equipped with an Islamic Performance Ratio (IPR). Further,  the government also has a significant role in improving the performance achievemnet of Islamic banks through policies that support increasing market share, such as converting state-owned conventional banks into Islamic banks. The outcome of this research is to provide information to stakeholders of Islamic banks to use an additional ratio, namely IPR, to measure the performance of Islamic banks.